Management competencies at different organizational levels: A study of Tabriz University of Medical Sciences - Parisa Yoshari; Maryam Naghshi; Saeed Musavi; Rahim Khodayari-Zarnaq (Journal of Education and Health Promotion)
Managers should have the necessary competencies to achieve organizational goals. Employees have worked with different managers and have valid opinions about managerial competencies. The aim of studies is to investigate the managerial skills required at various managerial levels from the perspective of the Tabriz University of Medical Sciences (TBZMED) staff. This quantitative study was carried out in 2023. The statistical population included all employees of TBZMED. The census sampling method was used to select the participants A Likert questionnaire was created to measure the professional competencies of management. Before using the questionnaire, its validity and reliability were checked. All data were analyzed using SPSS version 22 and in this study, P-value less than 5% was considered statistically significant. 120 completed questionnaires were received from TBZMED employees. The findings showed that strategic thinking, goal orientation, and performance management are the most important skills for top managers to achieve organizational goals. For middle managers, team building and networking are essential skills. For basic managers, accountability, commitment, belonging, organization, planning, and coordination are key skills. In addition, analytical thinking, problem solving, innovation, and creative thinking are important skills for all levels of managers. The study found the competencies managers need to act well. By improving these competencies and communicating better, managers can increase organizational commitment and achieve goals.